PELATIHAN DAN PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN SAMPAH PLASTIK UNTUK MENDUKUNG EKONOMI SIRKULAR DI DESA SESETAN - I Putu Eka Indrawan; Ayu Aprilyana Kusuma Dewi; Gde Iwan Setiawan; I Kadek Juni Arta (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2024)
The village of Sesetan is known to have high artistic and cultural value in Bali and has been worldwide, with communities engaged in art and culture for a long time. The art of carving, barbecue performances, and carving is very popular with tourists. However, an increased standard of living leads to increased plastic waste, which is difficult to clean, disturbing appearance, and a source of disease. Information about how to turn plastic garbage into a high-value product is crucial to society. In Sesetan Village, a team of lecturers from the University of PGRI Mahadewa Indonesia conducted a Social Bakti to socialize and encourage people to transform plastic garbage into innovative and creative products. As a result of this activity, people learn how to manage plastic garbage, how to use it to make bags and pots of crops, and to make artworks of